Labor of Dionysus : a critique of the state-form - Hardt, Michael (Theory out of bounds, 1994)
"Labor is the living, form-giving fire," Marx wrote. "It is the transitoriness of things, their temporality, as their transformation by living time." How is it, then, that labor, with all its life-affirming potential, has become the means of capitalist di